ComputerWohnen. Zur Geschichte des Computers in Wohnumgebungen zwischen Arbeit und Assistenz
Unter welchen historischen Bedingungen und mit welchen Auswirkungen wurde der Computer zum Bestandteil des Wohnalltags? Und wie verhält es sich dabei mit Praktiken des Wohnens und Wohnungseinrichtens? Die Beiträger*innen werfen einen Blick auf die Computerisierung des Zuhauses und zeigen, wie sie sich vollzieht. Der Fokus ihrer Analysen liegt einerseits darauf, wie Arbeit und Assistenz das Wohnen im Hinblick auf den Computer prägen. Andererseits denken sie den Computer aus der Perspektive der Wohnumgebungen neu und geben so einen kompakten medienhistorischen Überblick über den Beginn des Smart Homes.
Keywords: Mediengeschichte; Digitale Medien; Design; Medien; Medienwissenschaft; Medienästhetik; Mediensoziologie; Medientheorie; Medienphilosophie; Architektur; Technikgeschichte; Technik; Kultur; Kulturwissenschaft; Kulturgeschichte; Kulturtheorie; Popkultur; Geschichte des 20. Jahrhunderts; Geschichtswissenschaft; Kultursoziologie; Gender Studies; Mode; Klang; Cultural Studies; Informatik

Experimental characterization and numerical analysis of the influence of the CED coating process on viscous fingering formation in hybrid-jointed mixed structures - Al Trjman, Mohamad; Beule, Felix; Teutenberg, Dominik; Meschut, Gerson; Riese, Julia (The Journal of Adhesion)
The joining of dissimilar materials, such as steel and aluminum, entails significant challenges during thermal curing processes due to differing coefficients of thermal expansion. This study addresses the formation of “viscous fingering” instabilities in structural adhesive joints, which are induced by thermally driven relative displacements during the liquid phase of the adhesive. Using a component-like specimen “bridge specimen,” the dependency of this phenomenon on process temperature and structural stiffness (rivet distance) was characterized. Experimental results reveal that while the relative displacement scales cubically with the free buckling length, the resulting adhesive area reduction follows an exponential trend, leading to a loss of effective bond area of up to 79%, which significantly compromises the joint strength in automotive applications. To predict these process-induced defects, a thermo-chemo-viscoelastic-viscoplastic adhesive model implemented in LS-DYNA was applied. The model combines curing kinetics, viscoelastic relaxation, and pressure-dependent plasticity and features a geometric damage parameter (D) that captures the adhesive area reduction caused by viscous fingering as an exponential function of the accumulated normal strain in the liquid phase. This damage parameter, calibrated on base-specimen level, was transferred to the component geometry. The simulation demonstrated high predictive accuracy with a maximum deviation of the adhesive area reduction of 3.1% compared to experimental data. This validates the model’s capability to predict manufacturing-induced damage in complex hybrid structures solely based on thermal boundary conditions.
Keywords: Adhesive area reduction; CED coating process; delta alpha problem; epoxy structural adhesive; influence of manufacture; multi-material design; numerical simulation (FEM); relative displacements; viscous fingering (saffman-taylor-instability).

Bridging Systems Theory and Information Systems: A Framework for Designing Complex Information Systems - Ibrahimli, Ulvi; Hemmrich, Simon; Winkelmann, Axel (Communication of the Association for Information Systems)
Information Systems (IS) is rooted in systems theory. Systems theory offers powerful concepts to address challenges of growing system complexity and non-systemic design approaches in information systems. Despite its systemic origins, systems theory remains a peripheral topic in IS. The study addresses this gap by introducing a comprehensive framework of 52 systems-theoretical concepts to guide the design of complex IS artifacts. We synthesize scattered systems knowledge from diverse disciplines to provide a unified level of abstraction for complex information system design. We apply the framework to a use case of business reputation systems to show how the systems lens informs the design of a novel, complex information system. We make three key contributions to the literature. First, the framework provides a common ground for interdisciplinary research in information system design. Second, it offers a unified level of abstraction grounded in systems theory that serves as a coherent basis for artifact design. Third, it demonstrates the potential of systems theory as a foundational justificatory knowledge base. Furthermore, we provide guidance on applying the framework across multiple modes of reasoning, alongside further application guidelines. The study thus serves as a bridge between the body of systems knowledge and contextual design in IS.
Keywords: Information Systems Research; Systems Theory; System Complexity; System Design; Design Science

A blockchain-based reputation system for consulting - Hemmrich, Simon; Nissen, Volker (Advanced Studies in Consulting Research and Digitalization – A Scientific Update on the Digital Transformation of the Consulting Industry. Springer.)
Trust between client and consultant is perhaps the most important asset in con-sulting, as this is a highly intangible knowledge-intensive business that concerns is-sues of outstanding strategic and operational importance for the customers. Cli-ents who have not worked with a particular consultancy face considerable risk when they place an order while lacking reliable information about the service quality they can expect. There is a strong link between trust and reputation, as the positive reputation of a consultancy can act as a substitute for a new client’s missing individual experience with the provider, fostering trust in the service quali-ty. Thus, creating, maintaining, and demonstrating a good reputation is of signifi-cant importance for consultancies in a very competitive industry. To facilitate trustworthy signals, we design and implement a novel reputation mechanism that carries a monetary weight stored on a blockchain network as an immutable, decentralized, and transparent ledger. Based on an implementation in the Ethereum network and subsequent evaluation, we conclude that the reputation mechanism can contribute to leveling information asymmetry and reducing risk while increasing reputation and trust. The mechanism lends itself to being used in other business-to-business scenarios that suffer from similar information asymmetries.
Keywords: Reputation Systems; Consulting; Design Science Invention; Incentive; Blockchain; Monetary ratings; building trust; reduce information asymmetry consulting; B2B reputation system; consulting risk reduction; supplier evaluation system

Service through communication—Conceptualizing service systems with Luhmann’s systems theory - Beverungen, Daniel; Poeppelbuss, Jens; Hemmrich, Simon; Iqbal, Taskeen (Electronic Markets)
Service research has evolved into an interdisciplinary research field that bridges diverse disciplines, including information systems (IS) and marketing. Nearly two decades ago, the service system concept was introduced as a foundational abstraction in service research, drawing on ideas from the service-dominant logic (S-D logic) of marketing. Despite its widespread adoption in service research, particularly in the IS discipline, the service system concept lacks a solid theoretical foundation. This has resulted in conceptual ambiguity and overlap with related constructs, such as service ecosystems. Moreover, it has largely remained a static analytical lens, insufficiently capturing dynamic service phenomena, including value co-creation and co-destruction, as well as the emergence of institutional arrangements. To address these limitations, we propose Luhmann’s systems theory (LST) as a robust framework for conceptualizing service systems as autopoietic (self-creating) systems, in which communication serves as the fundamental mechanism that drives value co-creation. We derive five theoretical propositions from this re-conceptualization that clarify conceptual ambiguity and allow researchers to explore dynamic service phenomena in greater depth. Given LST’s general approach, our conceptualization provides a theoretically grounded, interdisciplinary foundation for advancing service research.
Keywords: Service system; Service ecosystem; Systems theory; Service research

Particle-Reinforced Aluminium Solid Self-piercing Rivets for Joining Aluminium Alloy Sheets - Koch, Steffen; Weber, Joshua; Meschut, Gerson; Stadelmann, Claudia; Böhm, Wolfgang; Merklein, Marion (Proceedings in Engineering Mechanics)
The use of aluminium materials in the structural and bodywork areas of assemblies has proven to be a targeted option for lightweight design. How-ever, the reliable and cost-efficient joining of aluminium components remains a challenge. Mechanical joining methods, such as riveting, are frequently used in the automotive and aerospace construction industries. Rivets are made from heat-treated steels. Compared to steel, the use of aluminium materials for fasten-ers offers several advantages in terms of joining properties, particularly in terms of recyclability, corrosion resistance and reduced weight of the joined structure. Additionally, the manufacturing process is shorter since aluminium fasteners do not require coating. However, aluminium rivets can often not be used due to the insufficient mechanical strength of the fastener material in relation to the joining component materials. This study systematically investigates the requirements for using solid alu-minium self-piercing rivets. The influence of rivet geometry adjustments on the joint quality is analysed using numerical simulation. The results are used to derive and evaluate an optimised rivet geometry for joining pure aluminium sheets. On this basis, solid self-drilling rivets with optimised geometry are manufactured from particle-reinforced aluminium produced in a continuous extrusion process by machining. The integration of particles increases the material’s strength. Exper-imental tests are conducted to evaluate the use of optimised solid self-piercing rivets. The quality-relevant parameters are determined and evaluated based on macrographs of the joints.
Keywords: Solid self-piercing riveting cdot particle-reinforced aluminium cdot continuous powder extrusion cdot Joining technology cdot Rivet geometry cdot lightweight design

Leveraging extreme-scale simulation data: a workflow framework for multidisciplinary simulator integration - Gräßler, Iris; Döhner, Niklas (Proceedings of the Design Society)
ABSTRACT: Engineers simulate system behavior to support decisions in product engineering. Leveraging such engineering simulation data in strategic product planning can support idea generation and early evaluation of design alternatives and limitations. However, limited resources and expertise hinder broader uptake in strategic product planning. This paper investigates simulator integration into automated workflows and key processing components to enable simulation without in-depth expertise. This approach improves strategic product planning by creating data-based decision support.
Keywords: simulation-based design; design tools; multi-/cross-/trans-disciplinary approaches; simulation data reuse

Inscription of power dynamics in platformized classrooms. Exploring coded spaces of platform architectures through Participatory Action Research - Schmidt, Rebecca (Learning, Media and Technology)
Platforms contribute to the ‘world-making’ of education; they play a co-constitutive role by envisioning and inscribing the functionalities anticipated in education. As programmable digital architectures, they both shape and are shaped by teachers’ and students’ practices. Building on two Action Research projects in German schools, the article concentrates on the reproduction of inequality within platformized classrooms. It uses the focus point of translation software usage to explore inscriptions into digital architectures. Analysing breakdowns of translation software usage among students who speak German as a second/foreign language, the article focuses on inscribed power dynamics within translation software, the mismatch between students’ practices and the imagined user, and the discrepancy between software logics and the educational setting. Discussing teachers’ invisible work, care and belonging in platformized education settings, the article highlights the epistemic inscriptions within technology. It describes how dataveillance and testing break down when students use translation software, thereby highlighting teachers’ shift towards creating a collective understanding. Lastly, the article discusses teachers’ autonomy within post-platform education by highlighting the limitations of currently available software products and software production.
Keywords: Intersectionality; platform studies; action research; post-platform education; breakdowns; translation software; classroom reserach

The power of combined modalities in interactive robot learning - Beierling, Helen; Beierling, Robin; Vollmer, Anna-Lisa (Frontiers in Robotics and AI)
This study contributes to the evolving field of robot learning in interaction with humans, examining the impact of diverse input modalities on learning outcomes. It introduces the concept of "meta-modalities" which encapsulate additional forms of feedback beyond the traditional preference and scalar feedback mechanisms. Unlike prior research that focused on individual meta-modalities, this work evaluates their combined effect on learning outcomes. Through a study with human participants, we explore user preferences for these modalities and their impact on robot learning performance. Our findings reveal that while individual modalities are perceived differently, their combination significantly improves learning behavior and usability. This research not only provides valuable insights into the optimization of human-robot interactive task learning but also opens new avenues for enhancing the interactive freedom and scaffolding capabilities provided to users in such settings.
Keywords: human-robot interaction; human-in-the-loop learning; reinforcement learning; interactive robot learning; multi-modal feedback; learning from demonstration; preference-based learning; scaffolding in robot learning

Development and Implementation of Diversity Programs in Large Collaborative Research Projects: An Example From Germany - Lorke, Mariya; Amelung, Rena; Kuchling, Peter; Paaßen, Benjamin; Pein-Hackelbusch, Miriam; Schloots, Franziska Margarete; Schulz, Klara; Nauerth, Annette (Diversity & Inclusion Research)
ABSTRACT In recent years, there has been an increasing awareness of the importance of incorporating diversity into research projects, focusing on both how they are conducted and their content. Funding organizations have started to require that research applicants pay attention to inclusion and diversity by considering gender dimensions and other diversity factors in their project plans and ensuring gender equality during execution. Based on an extensive literature research and expert discussions on how to develop and implement diversity strategies in large collaborative research projects, we argue that there is a lack of practical advice in existing literature. Drawing from our own experiences in conceptualizing and implementing a Diversity Program across four universities in Germany, we propose a framework for effectively integrating diversity into collaborative research initiatives across various academic fields.
Keywords: collaborative research projects; diversity strategy; gender equality

Continuous value shaping: A boundary concept for innovating service innovation approaches - Böhmann, Tilo; Roth, Angela; Satzger, Gerhard; Benz, Carina; Beverungen, Daniel; Boes, Andreas; Breidbach, Christoph; Gersch, Martin; Gudergan, Gerhard; Hogreve, Jens; Kurtz, Christian; Langes, Barbara; et al. (Electronic Markets)
Technological advancements and evolving value orientations reshape future value creation and pose new requirements for service innovation. While a variety of disciplines are developing new approaches to drive service innovation, this is primarily done in isolation and generates only fragmented solutions. Sociological theory has proposed “boundary objects” as an effective umbrella for communication and cooperation among communities. Therefore, we introduce continuous value shaping (CVS) as a boundary object describing service innovation approaches along five principles. We reflect on this concept through the different disciplinary lenses of researchers in service marketing, information systems, service engineering, sociology of work, and innovation management. These perspectives highlight how the CVS principles already connect to discourses within the individual disciplines. However, the CVS concept will not only provide an umbrella to embrace existing activities in different academic disciplines. It also assists to identify research themes that will benefit from uniting the power of these disciplines, and it can serve as an integrating framework to conceptualize complex service innovation approaches. Thus, the CVS concept should guide both researchers and practitioners to develop and implement novel innovation and transformation efforts—in and across organizations.
Keywords: Continuous value shaping (CVS); Service research; Service innovation; Digitalization; Sustainability; Interdisciplinary research

Poster: Computer Security Researchers' Experiences with Vulnerability Disclosures - Sri Ramulu, Harshini; Rotthaler, Anna Lena; Rossel, Jost; Gonzalez Rodriguez, Rachel; Wermke, Dominik; Fahl, Sascha; Kohno, Tadayoshi; Somorovsky, Juraj; Acar, Yasemin (Proceedings of the 2025 ACM SIGSAC Conference on Computer and Communications Security)
Vulnerability disclosures are necessary to improve the security of our digital ecosystem. However, they can also be challenging for researchers: it may be hard to find out who the affected parties even are, or how to contact them. Researchers may be ignored or face adversity when disclosing vulnerabilities. We investigate researchers' experiences with vulnerability disclosures, extract best practices, and make recommendations for researchers, institutions that employ them, industry, and regulators to enable effective vulnerability disclosures.
Keywords: software vulnerabilities; vulnerability disclosure; security research

A rate-based model for reactive separation columns with sandwich packings - Franke, Patrick; Schubert, Markus; Hampel, Uwe; Kenig, Eugeny Y. (Chemical Engineering Science)
Sandwich packings are assembled from two conventional structured packings with different geometrical surface areas stacked alternatingly within a separation column. When operated under partially flooded conditions, they provide significant mass transfer improvement compared to common structured packings. In this work, a rate-based model including novel mass transfer correlations is presented and validated using a comprehensive experimental database for the reactive absorption of CO2 into aqueous monoethanolamine. The proposed rate-based approach is capable of accounting for axial dispersion, thereby enabling the evaluation of the effect of liquid-phase backmixing on the mass transfer performance. The validated rate-based model is used to evaluate the separation performance of sandwich packings. Compared with structured packings, up to 10 % higher mass transfer rates are obtained.
Keywords: Sandwich packings Structured packings Rate-based approach Model validation Ultra-fast X-ray tomography

Fostering self-regulated entrepreneurial learning in entrepreneurship education - Fahrbach, Manuel; Jenert, Tobias; Fust, Alexander; Bellwald, Noah; Winkler, Christoph (Annals of Entrepreneurship Education and Pedagogy - 2025)
Keywords: Self-Regulated Learning; Entrepreneurship Education; Entrepreneurship Research

Transferability as a key to impactful entrepreneurship education outcomes: a new quest - Winkler, Christoph; Jenert, Tobias; Fust, Alexander (Annals of Entrepreneurship Education and Pedagogy - 2025)
Keywords: Methodology; Entrepreneurship Education; Entrepreneurship Research

Secure Distributed State Management for Stateful Signatures with a Practical and Universally Composable Protocol - Blömer, Johannes; Bröcher, Henrik; Krummel, Volker; Porzenheim, Laurens Alexander
Stateful signatures like the NIST standardized signature schemes LMS and XMSS provide an efficient and mature realization of post-quantum secure signature schemes. They are recommended for long-term use cases like e.g. firmware signing. However, stateful signature schemes require to properly manage a so-called state. In stateful signature schemes like LMS and XMSS, signing keys consist of a set of keys of a one-time signature scheme and it has to be guaranteed that each one-time key is used only once. This is done by updating a state in each signature computation, basically recording which one-time keys have already been used. While this is straightforward in centralized systems, in distributed systems like secure enclaves consisting of e.g. multiple hardware security modules (HSMs) with limited communication keeping a distributed state that at any point in time is consistent among all parties involved presents a challenge. This challenge is not addressed by the current standardization processes. In this paper we present a security model for the distributed key management of post-quantum secure stateful signatures like XMSS and LMS. We also present a simple, efficient, and easy to implement protocol proven secure in this security model, i.e. the protocol guarantees at any point in time a consistent state among the parties in a distributed system, like a distributed security enclave. The security model is defined in the universal composabilty (UC) framework by Ran Canetti by providing an ideal functionality for the distributed key management for stateful signatures. Hence our protocol remains secure even if arbitrarily composed with other instances of the same or other protocols, a necessity for the security of distributed key management protocols. Our main application are security enclaves consisting of HSMs, but the model and the protocol can easily be adapted to other scenarios of distributed key management of stateful signature schemes.
Keywords: distributed state; hash-based signature; stateful hash-based signature; universal composability; secure enclave

Towards Practicable Algorithms for Rewriting Graph Queries Beyond DL-Lite - Löhnert, Bianca; Augsten, Nikolaus; Okulmus, Cem; Ortiz, Magdalena (The Semantic Web - 22nd European Semantic Web Conference, ESWC 2025, Portoroz, Slovenia, June 1-5, 2025, Proceedings, Part I)
Despite the advantages that the virtual knowledge graph paradigm has brought to many application domains, state-of-the-art systems still do not support popular graph database management systems like Neo4j. Their query rewriting algorithms focus on languages like conjunctive queries and their unions, which were developed for relational data and are poorly suited for graph data. Moreover, they also limit the expressiveness of the ontology languages that admit rewritings, restricting them to those that enjoy the so-called FO-rewritability property. Rewritings have thus focused on the DL-Lite family of Description Logics. In this paper, we propose a technique for rewriting a family of navigational queries for a suitably tailored fragment of ELHI. Leveraging navigational features in the target query language, we can include some widely-used axiom shapes not supported by DL-Lite. We implemented a proof-of-concept prototype that rewrites into Cypher queries, and tested it on a real-world cognitive neuroscience use case with promising results.
Keywords: Ontology-based Data Access; Property Graphs; Navigational Queries

Life cycle engineering of lightweight structures in vehicles for on-demand mobility services - Ostermann, Moritz; Dierkes, Eric; Marten, Thorsten; Tröster, Thomas (Cleaner Engineering and Technology)
To reduce transport-related environmental impacts, innovative mobility system approaches such as on-demand services are being developed. These can include operating vehicles that differ regarding their characteristics and application profile from privately owned cars in motorized individual transport. Studies on life cycle assessment and life cycle engineering of vehicle lightweight structures are mainly limited to these privately owned cars and the impact category of climate change. In this paper, a method for life cycle assessment-based engineering of lightweight structures in vehicles for various mobility system applications, including on-demand mobility services, is developed. The method enables the holistic life cycle assessment of lightweight structures in different mobility system applications considering parameter changes at the upstream products, component, subsystem, vehicle and mobility system levels, as well as the integration of results into engineering activities. A case study is used to show that the vehicle and mobility system application of lightweight structures can significantly influence their environmental impacts and the selection of ecologically preferable product designs. The application in vehicles for on-demand mobility services can lead to an increase in absolute use stage energy demand and environmental impacts compared to applications in privately owned vehicles for motorized individual transport. However, normalized to the transport performance provided, the lifecycle environmental impacts of structural components in vehicles for on-demand mobility services can be lower than in vehicles for motorized individual transport. The paper contributes methodically and with quantitative results to improved decision making in life cycle engineering activities for lightweight structures in mobility system applications.
Keywords: Life cycle assessment; Life cycle engineering; Lightweight design; On-demand mobility; Shared mobility; Mobility services

Test-oriented Resilient Requirements Engineering (ToRRE): extending model-based effect chain analysis to verification objectives - Gräßler, Iris; Ebel, Marcel (Proceedings of the Design Society)
Verification and Validation (V&V) are essential processes in engineering Cyber-Physical Systems. However, the role of V&V engineers is often not given sufficient attention. Based on a systematic literature analysis and practical observations, a four-step method for Test-oriented Resilient Requirements Engineering (ToRRE) is developed. The steps are planning V&V, executing V&V activities, documenting V&V activities and analyzing results of V&V activities. Applying ToRRE ensures continuous information flow and traceability. Engineers are enabled to analyze requirements using engineering artifacts connected through Model-Based Systems Engineering. Adopting methods for Model-Based Effect Chain analysis to evaluated test cases and test scenarios, conclusions on requirements engineering and change management are enabled. The method is evaluated in an EU research project.
Keywords: systems engineering (SE); product modelling/models; design methods; verification & validation; test cases & test scenarios

Single-step self-punching lockbolt process for aluminum sheets without pre-hole - Han, Daxin; Kappe, Fabian; Vorderbrüggen, Julian; Jendrny, Jörg; Gorr, Eugen; Meschut, Gerson (Journal of Manufacturing Processes)
Keywords: Industrial and Manufacturing Engineering; Management Science and Operations Research; Strategy and Management